Pandemics, politics, and the resilience of employment relations research. (2nd October 2021) - Hodder, Andy; Martínez Lucio, Miguel
ABSTRACT: The Covid-19 pandemic has profoundly altered people's experiences of work around the world. In doing so, the crisis has appeared to change the public narrative on work and employment, and consequently has highlighted the continued relevance and value of employment relations as a field of study, in terms of both policy and research. In this paper, we reflect on the implications of the Covid-19 outbreak for the field of employment relations. We argue that the current crisis has highlighted the resilience of the field of employment relations, reminding us of its critical relevance to academic and public interest (although for how long is another matter). However, this can only be understood in the context of the broader dynamics and issues facing this field of study. We outline the challenges faced by academics and practitioners working in this area to build upon this new found attention to ensure that employment relations issues remain central in terms of research, teaching and public policy.